ANALISIS PROMOSI KESEHATAN DI PUSKESMAS KALIJUDAN TERHADAP PHBS RUMAH TANGGA IBU HAMIL - Intan Indah Kartika Sari; Muji Sulistyowati (Jurnal Promkes: The Indonesian Journal of Health Promotion and Health Education, 2015)
Infectious and non-infectious disease, Infant Mortality Rate (IMR) and Maternal Mortality Rate (MMR) are indicators of health status that their achievements have not been satisfactory. Various problems are closely related to behavioral factors. Behaviors that have a role in maintaining and improving health status is a Clean and Healthy Behavior (PHBS). However, the successful achievement of indicators PHBS is still far from the expected target. The aim of this study was to analyze the role of health promotion in the public health centers with the achievement of PHBS in pregnant women’s households. This study was an observational analytic with quantitative and qualitative approach. Quantitative approach with a sample of pregnant women, whereas qualitative informant was health promotion staff. Sampling was simple random sampling technique. This study used Pearson correlation test on quantitative data indicate that there was a relationship between health promotion of public health centers with the achievements of PHBS. Signifi cant value was 0.000 (α = 0.05). Qualitative study foundthat the role of health promotion in the health centers with PHBS achievement were realized through a series of health promotion programs, namely home visits, empowerment through partnerships, as well as organizing through UKBM.Keywords: health promotion, PHBS, pregnant women